2013
DOI: 10.1111/jocs.12216
|View full text |Cite
|
Sign up to set email alerts
|

Modified Bentall Procedure with Composite Biologic Grafts

Abstract: Our experience with Gen2 CBG showed decreased operative times and a trend toward improved survival, though further patient follow-up and larger sample sizes in prospective studies are necessary. Further research with this CBG and additional improvements are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Peak transvalvular gradient at hospital discharge was 20.03 ± 6.09 mmHg (range 11-39 mmHg). related to the adopted double sewing ring technique [17,18]. Taking advantage from other's and our personal experience with more than 120 implants of 3F prosthesis, a stentless valve made by three equal sections of equine pericardium assembled in a tubular structure on a thin polyester sewing ring [19], we began to implant the self-assembled 3F bioroot in 2010, using the previously described surgical technique.…”
Section: Resultsmentioning
confidence: 99%
“…Peak transvalvular gradient at hospital discharge was 20.03 ± 6.09 mmHg (range 11-39 mmHg). related to the adopted double sewing ring technique [17,18]. Taking advantage from other's and our personal experience with more than 120 implants of 3F prosthesis, a stentless valve made by three equal sections of equine pericardium assembled in a tubular structure on a thin polyester sewing ring [19], we began to implant the self-assembled 3F bioroot in 2010, using the previously described surgical technique.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we think it is better to sew between the cuff and the aortic annulus rather than to sew the sewing ring with the annulus. Yang et al 14 reported an alternative technique of performing the proximal anastomosis with continuous sutures between the Dacron graft and the aortic annulus, this technique could reduce the aortic cross-clamp time but the annulus tissue must be firm. Our study found that the commercially available graft significantly increased the risk of reoperation for bleeding and had worse survival outcomes compared to the self-assembled graft.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Until now, there are numerous modifications of the original Bentall procedure to reduce postoperative bleeding and other conduit-related complications. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Among those, Kouchoukos et al 5 described the "button technique" in which two coronary ostia were detached, adequately mobilized, and reattached to the conduit. This modified technique has been shown to reduce the risk of pseudoaneurysm in the proximal anastomosis and coronary ostia due to suture dehiscence.…”
Section: Introductionmentioning
confidence: 99%
“…A stentless bio‐Bentall operation may represent, in young and active patients who wish to avoid anticoagulation, 6–9 a valid alternative to homograft, often difficult to supply in most cardiac units, 10 and to the Ross operation 11 that requires a certain amount of surgical training and skill. Valve sparing procedures, introduced by David 3 and Yacoub 4 in the early 1990s, remain a valid alternative to Bentall in selected cases, and have proven excellent long‐term results in several reported large series of patients 12 .…”
Section: Discussionmentioning
confidence: 99%